Dissemination of research findings in public health among science and technology professionals in China - Jing LIU; Yi-luan HU; Xue-jun YIN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate the dissemination of research findings in public health and its influencing factors among science and technology professionals in China. MethodsAn online survey was conducted in January 2022 among 1 466 science and technology professionals recruited from Chinese Preventive Medicine Association, Chinese Nutrition Society, Chinese Antituberculosis Association, and Chinese Association of STD and AIDS Prevention and Control. The information on the professionals' research experience, working years, academic papers published, ways of funding support to dissemination, training experience in dissemination and implementation (D&I) research, and work experience in research-related setting were collected and associations of the professionals' characteristics with dissmination of research findings were analyzed. ResultsValid responses were collected from 956 (65.2%) of the professionals recruited and of the valid respondents, 737 reported being engaged in researches. For all the 737 respondents conducting research works, 58.1 % stated ever having disseminated their research findings, while the proportions of ever conducting the dissemination were 64.3%, 64.4%, and 67.8% for the respondents spending most of working time in research practice, doing research work for more than 20 years, and having published more than 6 academic papers during past 3 years, respectively. The respondents with following characteristics were more likely to conduct the dissemination of research finding: receiving funds that support to the disseminations through various ways (odds ratio [OR] = 2.39, 95% confidence interval [95% CI]: 1.61 - 3.54), ever taking a part in D&I research-related training (OR = 2.05, 95 % CI: 1.36 - 3.09), and having work experience in a practice or policy setting (OR = 5.38, 95% CI: 3.75 - 7.73) according to the results of multivariate binary logistic regression analysis. ConclusionA lot of effort is required for promoting the dissemination of scientific research findings among Chinese science and technology professionals in public health.